Deposition Efficacy of Natural and Synthetic Antioxidants on Fabrics - Paola Giannì; Heiko Lange; Giulia Bianchetti; Conny Joos; David W. Brogden; Claudia Crestini (Applied Sciences, 2020)
Pine bark extracts were tested as valid natural alternatives to common phenolic antioxidants to be deposited onto solid matrices. An analytical method for determining both deposition-efficacy and maintenance of antioxidant activity on fabrics surfaces was developed and successfully applied to phenolic antioxidants and pine tannins onto cotton fabric samples. Accumulated data suggest that common phenolic antioxidants and tannin contribute to an elevated antioxidant activity on fabric. A known source of odour is autoxidation of residual sebum on fabric, leading to the generation of malodourous compounds. Therefore, antioxidants hold the promise for mitigating malodour on fabrics, a top unmet consumer need around the globe.